Adequacy of nutrition and body weight in patients with early stage dementia: The cognition and aging study. Issue 5 (October 2019) - Hsiao, Hua-Tsen; Lee, Jun-Jun; Chen, Hsiu-Hui; Wu, Ming-Kung; Huang, Chi-Wei; Chang, Ya-Ting; Lien, Chia-Yi; Wang, Jing-Jy; Chang, Hsin-I; Chang, Chiung-Chih
Summary: Background & aims: Recent evidence highlights the effects of obesity, diabetes and hypertension in the development of Alzheimer's disease. Involuntary body weight changes in patients with different stages of dementia can be related to clinical factors of the patient per se or support from their caregivers. Understanding the interactions among factors is important to establish a monitoring paradigm to guide treatment strategies. Methods: A total of 345 patients with very mild (n = 224) and mild stage (n = 121) dementia were enrolled from a multi-disciplinary dementia clinic. Clinical data (comorbidities, Mini-Mental State Examination [MMSE] scores, neuropsychiatric inventory [NPI] scores, eating behavior questionnaire), nutritional state (Mini-Nutritional Assessment [MNA] or MNA short form [MNA-SF]) and body mass index (BMI) were recorded. Nutritional state and BMI served as the two major outcome measures, and factors for analysis included diagnosis, dementia severity and clinical data. Results: There was a significant correlation between MNA-SF and MNA (r = .898, p < 0.01), but a 24% mismatch in case dislocation was found using the at-risk or malnutrition criteria. Factors related to obesity included male sex, higher MNA-SF and MNA scores, diabetes mellitus and hypertension, while acceptable discrimination for obesity (BMI≧23 kg/m 2 ) was obtained with a MNA-SF score of 12/13 or MNA score of 21/22. NPI was the only independent factor related to both MNA-SF (β = −.06, P < 0.001) and MNA (β = −.1, P < 0.001). A BMI of 22–23 kg/m 2 was adequate in this group of patients with early stage dementia from nutritional and comorbidity perspectives. After controlling for BMI, the patients with advanced dementia had higher swallowing problem and appetite change scores. Conclusions: In these patients with early stage dementia, a higher BMI indicated adequate nutritional status and higher MMSE, but also higher rates of comorbidities, diabetes mellitus and hypertension. Highlights: Involuntary body weight changes in patients with dementia reflected the stage of dementia or caregiver support. NPI scores significantly predicted MNA and MNA-SF scores. In the patients with dementia, BMI reflected nutrition, MMSE and number of comorbidities. Considering comorbidities and nutritional status, a BMI of 22–23 kg/m 2 may be considered as adequate in dementia patients.